Children and adolescents with marginal zone lymphoma have an excellent prognosis with limited chemotherapy or a watch‐and‐wait strategy after complete resection. Issue 4 (29th December 2017) - Ronceray, Leila; Abla, Oussama; Barzilai‐Birenboim, Shlomit; Bomken, Simon; Chiang, Alan KS; Jazbec, Janez; Kabickova, Edita; Lazic, Jelena; Beishuizen, Auke; Mellgren, Karin; Tanaka, Fumiko; Pillon, Marta; et al.
Abstract: Data on management of pediatric marginal zone lymphoma (MZL) are scarce. This retrospective study assessed characteristics and outcome in 66 patients who were <18 years old. Forty‐four (67%) had an extranodal MZL (EMZL), 21 (32%) a nodal MZL (NMZL), and one patient a splenic MZL. Thirty‐three patients (50%) received a variable combination of adjuvant chemotherapy/immunotherapy/radiotherapy, while the remainder, including 20 of 21 with NMZL, entered an active observation period. Overall survival was excellent (98 ± 2%), although 11 patients relapsed (17%; NMZL, n = 1; EMZL, n = 10), seven after any therapy and four after complete resection only. In conclusion, outcome of NZML, in particular, seems to be excellent after (in)complete resection and observation only.